The Diabetes Quality Improvement Project - Barbara Fleming; Sheldon Greenfield; Michael M. Engelgau; Leonard Pogach; Steven B. Clauser; Marian Parrott (2001)
BACKGROUND -As the worldwide diabetes epidemic continues to unfold, some experts have asked whether the war against it is being lost (1-3).In the U.S., blindness, kidney failure, amputations, and cardiovascular disease resulting from diabetes not only markedly reduce quality and length of life but also cost nearly $100 billion annually (4 -7).Fortunately, a vast body of research has clearly established that several effective treatments and practices may substantially reduce or prevent this burden (8 -19).These interventions, if broadly implemented, can allow us to use our health efforts and resources more effectively and efficiently to minimize the diabetes burden.Judging from the scant data available, however, the level of care currently delivered to populations with diabetes often may not produce the possible health-related gains (20,21).To assess more completely the level of diabetes care delivered in the U.S., we need standardized uniform performance measures that can assess quality of care accurately and reliably.These measures will enhance uptake of research into practice and may ultimately improve diabetes care and clinical outcomes.In the early to mid-1990s, many organizations developed performance measures for diabetes care, but the result was that providers were often required to collect and report many different, sometimes conflicting, measures, depending on their care delivery system.It was recognized that a national consensus on measures could enhance this process and provide a method for assessing care within and across health care settings while providing a meaningful mechanism for quality improvement (QI).In this review, we describe the Diabetes Quality Improvement Project (DQIP), which has developed and implemented a comprehensive set of national measures for evaluation and QI.HISTORY AND ORGANIZATIONAL STRUCTURE -In 1995, the Health Care Financing Administration (now known as the Centers for Medicare and Medical Services [CMS]) and the National Institute of Diabetes and Digestive and Kidney Diseases convened ϳ20 public and private health organizations with an interest in performance measurement for diabetes care (Fig. 1).The goal was to identify a strategy for developing a comprehensive measurement set for diabetes care that would be broadly accepted and widely implemented.Financial and logistical support were needed to create the DQIP, as was an organizational structure with broad representation from the private and public sectors as well as professional organizations, clinical and public health experts, diabetes researchers, and experts in methodology.In 1997, DQIP was founded jointly by CMS, the National Committee for Quality Assurance (NCQA), and the American Diabetes Association (ADA).CMS, which has long been committed to quality of care issues, provided financial support, and NCQA provided logistical support.An Operations Group was created of public and private sector organizations and agencies to provide general direction, and a Technical Expert Panel (TEP) was formed to develop quality performance measures.The organizational structure was designed to enhance nationwide adoption of the DQIP performance measures by giving the project scientific credibility, links to the medical community, and the commitment of organizations that pay for diabetes care.The Operations Group included the ADA, the Foundation for Accountability in Health Care (FACCT), CMS, NCQA, the American Academy of Family Practice (AAFP), the American College of Physicians-American Society of Internal Medicine (ACP-ASIM), the Centers for Disease Control and Prevention (CDC), and the Veterans Health Administration (VHA).Thus, the members included the majority of diabetes care providers in the U.S., the major health care organizations in which diabetes care is delivered, and the major payors for diabetes care, along with leading researchers in clinical diabetes and health services.Several of these organizations had already worked extensively on improving diabetes care, and many had developed specific quality measures.Each organization realized that joining DQIP